Early endosome antigen 1 (EEA1) decreases in macrophages infected with Paracoccidioides brasiliensis - Voltan, Aline Raquel [UNESP]; Sardi, Janaina de Cassia Orlandi [UNESP]; Soares, Christiane Pienna [UNESP]; Pelajo Machado, Marcelo; Almeida, Ana Marisa Fusco [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Oxford University Press (OUP), 2013)
Paracoccidioidomycosis (PCM) is a chronic granulomatous disease caused by the dimorphic fungus Paracoccidioides brasiliensis, endemic in Latin America. P. brasiliensis has been observed in epithelial cells in vivo and in vitro, as well as within the macrophages. The identification of the mechanism by which it survives within the host cell is fertile ground for the discovery of its pathogenesis since this organism has the ability to induce its own endocytosis in epithelial cells and most likely in macrophages. The study of the expression of endocytic proteins pathway and co-localization of microorganisms enable detection of the mechanism by which microorganisms survive within the host cell. The aim of this study was to evaluate the expression of the endocytic protein EEA1 (early endosome antigen 1) in macrophages infected with P. brasiliensis. For detection of EEA1, three different techniques were employed: immunofluorescence, real-time polymerase chain reaction (PCR) and immunoblotting. In the present study, decreased expression of EEA1 as well as the rearrangement of the actin was observed when the fungus was internalized, confirming that the input mechanism of the fungus in macrophages occurs through phagocytosis. © 2013 ISHAM.
Keywords: Early endosome; EEA1; Macrophages; Paracoccidioides brasiliensis; actin; early endosome antigen 1; F actin; actin filament; animal cell; controlled study; immunoblotting; immunofluorescence; macrophage; nonhuman; protein expression; real time polymerase chain reaction